Dust input from AGB stars in the Large Magellanic Cloud - Zhukovska, Svitlana; Henning, Thomas (Astronomy and astrophysics, 2013)
Aims: The dust-forming population of AGB stars and their input to the interstellar dust budget of the Large Magellanic Cloud (LMC) are studied with evolutionary dust models with the main goals (1) to investigate how the amount and composition of dust from AGB stars vary over the galactic history; (2) to characterise the mass and metallicity distribution of the present population of AGB stars; (3) to quantify the contribution of AGB stars of different mass and metallicity to the present stardust population in the interstellar medium (ISM). Methods: We used models of the stardust lifecycle in the ISM developed and tested for the solar neighbourhood. The first global spatially resolved reconstruction of the star formation history of the LMC from the Magellanic Clouds Photometric Survey was employed to calculate the stellar populations in the LMC.Results: The dust input from AGB stars is dominated by carbon grains from stars with masses ≲4 M⊙ almost during the entire history of the LMC. The production of silicate, silicon carbide, and iron dust is delayed until the ISM is enriched to about half the present metallicity in the LMC. For the first time, theoretically calculated dust production rates of AGB stars are compared with those derived from infrared observations of AGB stars for the entire galaxy. We find good agreement within scatter of various observational estimates. We show that the majority of silicate and iron grains in the present stardust population originate from a small population of intermediate-mass stars consisting of only ≲4% of the total number of stars, whereas in the solar neighbourhood they originate from low-mass stars. With models of the lifecycle of stardust grains in the ISM we confirm the strong discrepancy between dust input from stars and the existing interstellar dust mass in the LMC reported previously.
Gesehen am 28.07.2021